Sędziowie pokoju we Francji w czasach Rewolucji — zagadnienia ustrojowe a ideały oświecenia - Oskar Olejnik (Prawo)
The purpose of this paper is to answer the question of whether the philosophy of the Enlightenment inspired the organization of justices of the peace in France, and if so, to what extent. The National Assembly in 1790 was faced with the task of reorganizing the system of judicature (organization judiciaire). The work on the law, which was eventually passed as the law of August 16–24, 1790, led to the establishment of the institution of justices of the peace equipped with two areas of competence: litigation and conciliation. The manner of their selection and the lack of requirements for experience or education of candidates followed the demands of the Enlightenment, but other ideas were not fully employed.